Examining the Impact of a Blended Mobility Program on Pre-Service Language Teachers’ Critical Reflection: “Das tiefe Eintauchen sehe ich als einen kleinen ‘Schatz’” - Gerwers, Franziska; Gerns, Pilar; Brinkmann, Lisa Marie (Palgrave Macmillan, Cham, 2025)
Blended mobility (BM), which combines online and physical learning, is gaining traction in higher education as a means of preparing pre-service teachers for globally connected environments. It is considered to enhance professional skills such as critical reflection (CR). However, little empirical research has examined the effect of BM programs on student teachers’ CR. This chapter examines the impact of a BM program between a German and Spanish university on language student teachers’ CR. Students analyzed different school systems, explored diverse pedagogical approaches, documented their learnings in e-portfolios through reflective prompts and group reflections. These e-portfolios and reflections were used as data collection tools to examine students’ CR, employing a qualitative content analysis approach, which was guided by frameworks of CR, encompassing four levels (reporting, relating, reasoning, and reconstructing) and six dimensions (motivational, affective, bodily, personal, cognitive, and cultural). The findings indicate increased CR across all levels, especially in the cognitive and personal dimensions, closely linked to the affective and motivational ones. The individual and collective affordances provided a more holistic development of CR. However, while the student teachers engaged with various dimensions and levels of CR, they struggled to connect these insights to broader socio-economic, political, and historical contexts.
Keywords: blended mobility program; pre-service language teachers’ critical reflection; Das tiefe Eintauchen sehe ich als einen kleinen ‘Schatz’